Los quistes serosos solitarios del riñón. Relatos de cinco casos - Parra Bernal, Enrique; Bethencourt, O.; Molero Sánchez, J.; Vera Rodríguez, G.; Soto, Emonel (Investigación Clínica, 2013)
No presenta resumen